Clinical and Epidemiological Characteristics of Molluscum Contagiosum Cases Admitted to Our Dermatology Polyclinic - Saral, Yunus (Fırat University, 2002)
Aim: The aim of this study was to investigate the clinical and epidemiological characteristics of molluscum contagiosum (MC) cases admitted to our policlinic and followed as outpatients. Material and Methods: A total of 68 patients admitted to Dermatology Outpatient Clinic at Firat University, Faculty of Medicine, Firat Health Centre between the period of April 1999 and December 2000 and diagnosed with MC were enrolled to this study. Results: Of the 68 patients with MC, 36 (52.9%) were male and 32 (47.1%) were female and their age varied between 1-49 (mean 14.3±13.3) years. The most frequent localisation of lesions were at the trunk and extremities with the 27 (39.8%) cases. Head-neck area and genital area were followed with 21 (30.8%) and 20 (29.4%) cases, respectively. In 22 of the cases (32.3%) there was a history of MC in the family. The mean duration of lesions presence was 4.5 months which was varied in most of the patients (61.8%) between 15 days to 3 months. The number of lesions of the cases was ranged from 2-100 Conclusion: MC frequency were similar when investigated with respect to age and sex and all the cases were based on the skin, while the localisation of lesions were mainly in trunk and extremity in children, and in genital area in adults.

Amaç: Bu çalışma, polikliniğimizde izlenen molluskum kontagiyozum (MK) Olgularının klinik ve epidemiyolojik özelliklerini araştırmak amacı ile planlandı. Gereç ve Yöntem: Çalışma kapsamına Fırat Üniversitesi Tıp Fakültesi Fırat Tıp Merkezi Dermatoloji polikliniğine Nisan 1999-Aralık 2000 tarihleri arasında başvuran ve MK tanısı alan toplam 68 olgu alındı. Bulgular: Molluskum kontagiyozumlu 68 olgunun 36'sı (%52.9) erkek, 32'si (%47.1) kadın olup yaşları 1-49 (14.3±13.3) yıl arasında değişiyordu. Lezyonların en sık yerleşim yeri 27 (%39.8) olgu ile gövde ve ekstremiteler idi. Bunu 21 (%30.8) olgu ile baş-boyun bölgesi ve 20 (%29.4) olgu ile genital bölgenin izlediği saptandı. Olguların 22'sinin (%32.3) aile bireylerinde öykü vardı. Lezyonların devam süresinin ortalama 4.5 ay olduğu ve olguların çoğunda (%61.8) bu sürenin 15 gün-3 ay arasında değiştiği belirlendi. Olgulardaki lezyon sayısı 2-100 arasında değişmekte idi. Sonuç: Olgularımızda MK'nın görülme sıklığının yaşa ve cinsiyete göre benzer ve tüm lezyonların deri yerleşimli olduğu, çocuklarda gövde ve ekstremite, erişkinlerde genital tutulumun daha sık olduğu gözlenmiştir.
POLİKLİNİKTE İZLENEN MOLLUSKUM KONTAGİYOZUM OLGULARININ KLİNİK ve EPİDEMİYOLOJİK ÖZELLİKLERİ